Optimization of Indonesia's Ocean Policy: An Evidence-Based Evaluation and Recommendations (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
This research evaluates the effectiveness of Indonesia’s marine policies by integrating relevant socio-economic, demographic, and geographical considerations. The study was conducted across 18 Indonesian marine ecoregions, encompassing diverse coastal and archipelagic areas with varying governance characteristics. The study utilized a structured survey of 3,159 respondents to identify key governance challenges, including weak inter-agency coordination, high economic dependence of coastal communities, and implementation disparities between mainland and island regions. Instrument validity was ensured through cognitive interviews to test question clarity before distribution. Data analysis employed descriptive statistics, Pearson correlation, and multiple linear regression to quantify the relationship among policy effectiveness, communities’ economic resilience, and public support for conservation. A thematic qualitative analysis of in-depth stakeholder interviews further explored policy barriers and opportunities. Findings reveal that while communities participate in local policy initiatives (mean participation score of 3.52), their influence in decision-making remains limited (mean influence score of 3.19). Based on these evidence-based results, recommendations include enhancing institutional coordination, promoting marine-based economic diversification, and empowering coastal communities to build adaptive capacity in response to climate change and environmental degradation.